2016
DOI: 10.2134/jeq2015.09.0495
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Surface Transport of Urea-Nitrogen: A Rainfall Simulation Study

Abstract: Studies of harmful algal blooms and associated urea concentrations in the Chesapeake Bay and in coastal areas around the globe strongly suggest that elevated urea concentrations are associated with harmful algal blooms. The observed increased frequency and toxicity of these blooms in recent decades has been correlated with increased agricultural use of N inputs and increased use of urea as a preferred form of commercial N. This rainfall simulation study sought to assess the potential for different N fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
3
15
0
Order By: Relevance
“…The lack of research on this topic is largely due to the complexity of the mechanisms controlling N dynamics. Although most N losses from agricultural fields are typically associated with nitrate leaching and ammonia volatilization (Burkart and James, 1999; Lerch et al, 2015), the contribution of N in runoff has only recently being recognized as an important pathway of N transport (Pote et al, 2003; Diaz et al, 2010; Kibet et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The lack of research on this topic is largely due to the complexity of the mechanisms controlling N dynamics. Although most N losses from agricultural fields are typically associated with nitrate leaching and ammonia volatilization (Burkart and James, 1999; Lerch et al, 2015), the contribution of N in runoff has only recently being recognized as an important pathway of N transport (Pote et al, 2003; Diaz et al, 2010; Kibet et al, 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Two lines of evidence weigh in favor of the latter. First, given the rapid hydrolysis of urea‐N in soil (Cartes et al, 2009; Fisher et al, 2016, Kibet et al, 2016), all of the urea‐N that would have been applied to crops in the spring would have been transformed in the two or more months elapsed since application. Second, the most striking increases in urea‐N concentration occurred from 42 to 66 h and beyond (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rapid hydrolysis of urea‐N in soils generally precludes substantial export from fertilizer applications (Fisher et al, 2016). Losses via leaching and overland flow are brief and typically small even under heavy rainfall conditions (Han et al, 2015; Kibet et al, 2016). In a synoptic watershed study on the Delmarva Peninsula, Tzilkowski (2013) found no evidence that storms in the weeks after poultry manure application led to increased urea‐N in streams.…”
mentioning
confidence: 99%
“…However, it was difficult to determine whether this change was part of long-term downward trend in urea-N in the Manokin River and its tributaries, or simply an artifact arising from different monitoring strategies and/or sampling locations. Moreover, an increased focus on event-based sampling with high-frequency data from in situ sensors ) is also needed, since external urea-N inputs from the washoff of fertilizers and manures are highly ephemeral in time and space (Kibet et al 2016), and these urea-N transfers are often missed by routine grab sampling programs like the ones that were employed in our study and the study by Glibert et al (2005). Even so, the lack of continuous urea-N data during the intervening decade hampered our ability to assess plausible explanations for the urea-N differences between the two studies, including changes in external factors like hydroclimate, agricultural management, and waste treatment processes, as well as internal factors like nutrient cycling.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Effluxes of urea-N from marine sediments (Lomstein et al 1989;Therkildsen and Lomstein 1994) are also important, especially those that are facilitated by benthic bacteria (Pedersen et al 1993). Along with commercial fertilizers, urea-N is typically present in the excreta of livestock (Livingston et al 1962), producing added concerns over the washoff of urea-N from manures to surface waters (Kibet et al 2016). In terms of anthropogenic urea-N sources, commercial urea-N fertilizer has received the most attention , as its use in agriculture has increased by over two orders of magnitude since the 1960s and now comprises more than half of all N applied to croplands.…”
Section: Introductionmentioning
confidence: 99%